2012
DOI: 10.1103/physreve.86.011901
|View full text |Cite
|
Sign up to set email alerts
|

Collective dynamics of self-propelled particles with variable speed

Abstract: Understanding the organization of collective motion in biological systems is an ongoing challenge. In this paper we consider a minimal model of self-propelled particles with variable speed. Inspired by experimental data from schooling fish, we introduce a power-law dependency of the speed of each particle on the degree of polarization order in its neighborhood. We derive analytically a coarse-grained continuous approximation for this model and find that, while the specific variable speed rule used does not cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 45 publications
2
85
1
Order By: Relevance
“…This has been shown for instance by Gautrais et al [40], who detected a change in behavioural parameters with increasing density, leading to a disordered swimming once a critical density has been reached. It is worth noting that in that particular case, the individuals may change their behaviour relative to the density [91]. This additional coupling, namely the influence of the school as a whole on the behaviour of its constituent individuals, is a topic that we may carefully consider in future investigations.…”
Section: Determining Group Size Effects and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been shown for instance by Gautrais et al [40], who detected a change in behavioural parameters with increasing density, leading to a disordered swimming once a critical density has been reached. It is worth noting that in that particular case, the individuals may change their behaviour relative to the density [91]. This additional coupling, namely the influence of the school as a whole on the behaviour of its constituent individuals, is a topic that we may carefully consider in future investigations.…”
Section: Determining Group Size Effects and Theirmentioning
confidence: 99%
“…the school) is highly polarized [60]. This critical change in global behaviour is obtained by varying the value of a behavioural parameter such as noise [60,90], blind angle size [65], speed [91], alignment tendency [62] or a 'strategy parameter' [92], which weighs a behavioural compromise between aligning with neighbours and reacting to their direction changes. The validity of this view finds some support in the experimental work of Becco et al [93] that showed that such transition from disorder to order can be obtained by increasing the density of Tilapia fish in a shallow water arena.…”
Section: Statistical Physics Of Collective Motionmentioning
confidence: 99%
“…In recent years, a variety of efforts have been devoted to modeling the dynamic properties of swarms [15][16][17][18][19][20][21][22][23][24][25][26][27]. In 1995, Vicsek et al proposed a particularly simple but rich model [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, active matters in biological and physical systems have been studied theoretically and experimentally [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The kinetics of active particles moving in periodic structures could exhibit peculiar behaviors.…”
Section: Introductionmentioning
confidence: 99%